The Promising Key Factors Mediating Secondary Neuronal Damage in the Perihematomal Region of Intracerebellar Hemorrhage of Mice - Saandeep Bhatia; Ramissh Paramasivam; Mohd Khairul Izamil Bin Zolkefley; Regunath Kandasamy; Sangu Muthuraju; Jafri Malin Abdullah (Journal of Physiological Investigation)
The underlying mechanisms of secondary neuronal damage following intracerebellar hemorrhage (ICbH) have not yet been clearly understood. Our previous study reported apoptotic neuronal damage in the perihematomal region (PH) in mice. However, the possible key factors causing secondary neuronal damage in ICbH are not yet known. Therefore, we aimed to study the vital factors in the mediation of secondary neuronal damage following ICbH induced by collagenase type VII (0.4 U/μL of saline) into the cerebellum of mice. The mice were grouped into four groups: (1) control group (n = 12), (2) day-1 group (n = 12), (3) day-3 group (n = 12), and (4) day-7 group (n = 12). All mice underwent behavior assessment following induction of ICbH and were subsequently sacrificed on days 1, 3, and 7. Perihaematoma samples were collected to study morphological changes, immunohistochemistry, nitric oxide (NO) estimation, and oxidative stress markers, respectively. Mouse behavior was disturbed following ICbH on days 3 and 7 compared to the control. In addition, neuronal damage was found in the PH region. Glial fibrillary acidic protein (GFAP) and excitatory amino acid transporter 1 (EAAT1) were highly expressed on day 7, while gamma-aminobutyric acid receptor subunit alpha-1 (GABAAα1)-containing receptor subunit was detected on days 1 and 3. NO increased on day 1 post-induction and decreased on days 3 and 7. The expressions of superoxide dismutase (SOD), catalase (CAT), neuronal nitric oxide synthases (nNOSs), glutathione peroxidase 1, and cyclooxygenase-2 (COX-2) were significantly increased on day 3. Morphological studies of the PH and tissue showed that neuronal damage occurred from day 1 onward and peaked on day 3, associated with alterations in NO, reactive astrocytes (GFAP), glutamate transport regulation (EAAT1), and GABA receptor. Briefly, significant changes in the key markers in the PH regions at different time points are possibly crucial factors facilitating secondary neuronal damage in the PH region. Identifying the time window of these vital changes could help prevent secondary damage and optimize the treatment to occur at proper time points.